The Impact of Cooperative Learning Method on the Oral Proficiency of Learners of the Training Program for English Tourist Guides - Hong, Yao; Chen, Ling-Ge; Huang, Jian-Hao; Tsai, Yi-Ying; Chang, Te-Yi (Frontiers in Psychology, 2022)
Oral proficiency is the core element of training courses for English tourist guides. This ability needs to be addressed in training program for English tourist guides. Cooperative learning method is widely used by educators as a teaching method, but rarely used to improve oral proficiency. A quasi-experimental design involving 60 participants was conducted to investigate and examine the effectiveness of cooperative learning method on the oral proficiency of learners in the English tourist guide training program. There were 30 learners in the control group and the experimental group respectively. The experimental group adopted cooperative learning method, while the control group adopted traditional approach, in both of which pre-test and post-test were conducted. The results of the study showed that the impact of teaching with the cooperative learning method on the oral proficiency of learners of the training program for English tourist guides was higher than that of teaching with the traditional approach. The importance of the cooperative learning method in the training program for English tourist guides is highlighted as a reference for educational institutions.